Analisis Kepemimpinan Serta Lingkungan Kerja Dalam Meningkatkan Kinerja Karyawan Ditjen Beacukai Malang - IRIANI YUDANINGRUM, BUDI; KOSLANI; Ali Tamrin, Muhamad (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
In general, research objectives include: To obtain new knowledge or discoveries. To find out whether job analysis has a simultaneous effect on performance achievement. To find out whether Job Specifications have a partial effect on performance achievement. To find out how influential Job Analysis and Job Specifications are on performance achievement at the Malang Regency Manpower, Transmigration, and Social Service. The research approach used in this research is quantitative. The research location is the place where the research is carried out. Determination of research location. This is a very important stage in qualitative research because determining the research location means that the object and objectives have been determined, making it easier for the writer to carry out the research. Thus, researchers conducted research at the Malang Customs and Excise Office which is located at Raya Situbondo No.37, Lkr. Kp. Baru, Bulusan, Kec. Kalipuro, Malang Regency, East Java 68451.The results of this research are that the first hypothesis can prove that, leadership variables, work discipline, and work environment, simultaneously influence the performance of Malang Customs and Excise employees. Testing the second hypothesis proves that partially the leadership and work discipline variables do not have a significant effect on the performance of Malang Customs and Excise employees, while the work environment variable is proven to have a positive and significant effect on the performance of Malang Customs and Excise employees. The Adjusted R Square results are still low at 14.7 percent in the research. And the data obtained from respondents is very small so it is susceptible to Normality problems when processing the data. The data should have been 92 respondents, but the researchers only got 52 respondents, this happened because the COVID-19 situation still exists which requires employees to carry out health protocols and several Customs and Excise employees are carrying out services outside the region.